Social Policy Trends: the Homelessness Income Cut Off - Ronald Kneebone (The School of Public Policy Publications)
Homelessness is an increasingly important public policy issue. Yet policymakers have not had a measure of the income required to keep people from experiencing homelessness. Until now.